Drying Characteristics of Cooked Jasmine Brown Rice and True Densities of Dried Products - Le, Tuan Quoc; Jittanit, Weerachet (Agriculture and Natural Resources, 2012)
Drying is a vital process for manufacturing instant brown rice. In this study, cooked jasmine brown rice was dried using various drying methods comprising single-stage drying by a hot-air dryer (HAD) and a microwave dryer (MWD) and two-stage drying using a MWD in the first stage and then a HAD, a fluidized bed dryer (FBD) and a MWD for the second stage. The main objective was to investigate the drying kinetics, effective moisture diffusivities and true densities of cooked brown rice dried in a FBD, a HAD and a MWD. The results proved that a MWD provided the highest drying rate when compared to its counterparts. The drying experimental data were well-fitted to the empirical equations. The moisture diffusivities of cooked brown rice during drying depended on the moisture transport mechanism occurring inside the rice kernel. The moisture diffusivities were much higher for microwave drying than hot-air drying. The true densities of samples that were dried in the HAD were higher than those dried in the MWD indicating a more porous structure in the microwave-dried samples.